Evaluating the Utility of Follow-up Radiographs for Isolated Radial Head Fractures Undergoing Initial Nonoperative Treatment. Issue 8 (August 2019) - Fenoglio, Amy K.; Stephens, Andrew R.; Zhang, Chong; Presson, Angela P.; Tyser, Andrew R.; Kazmers, Nikolas H.
Abstract : Objectives: To evaluate the utility of follow-up radiographs in patients with isolated partial articular radial head fractures (OTA/AO 2R1B1 or 2R1B3). Design: Retrospective cohort study. Setting: Academic Level 1 Trauma Center. Patients: Adult patients (≥18 years) with isolated partial articular radial head fractures indicated for initial nonoperative treatment. Intervention: Analysis of elbow radiographs at initial presentation and at postinjury follow-up of 3–8 weeks. Variables Measured: Articular gap and step-off. Main Outcome Measure: Radiographic articular displacement between initial and follow-up radiographs. Results: For 72 included patients, initial radiographs were obtained on average 2.6 days after injury and follow-up radiographs 33.7 days thereafter. Equivalence tests evaluating gap and step-off thresholds of <1 mm were both significant, indicating that the cohort displaced <1 mm for both parameters between initial and follow-up radiographs. No patients proceeded to surgical treatment following the repeat radiographs. Conclusions: These fractures do not displace in the early postinjury period, as defined as a <1 mm of change in both intra-articular gap and step-off, as compared to initial radiographs. Routine follow-up radiographs for these injuries is a source of cost, but with limited utility in detecting interval displacement or leading to a change in management. Selective use of radiographs to evaluate specific clinical concerns may lead to cost savings. Level of Evidence: Diagnostic Level IV. See Instructions for Authors for a complete description of levels of evidence.